Focus Issue: addressing challenges of hazards, risks, and disaster management in mountain regions - Szarzynski, Jörg; Alcántara-Ayala, Irasema; Nüsser, Marcus; Schneiderbauer, Stefan (Mountain research and development, 2022)
Mountain Research and Development publishes research on topics related to mountains, mountain people and communities, and sustainable development in mountains.